The Implementation of Active and Creative Learning Methods at Al-Ikhlas TPA in Kemuning District, Palembang City - Yuni Farlina; Putri Aprilia Sari; Annisa Rahmadini; Ananda Putri; A’yuni Syaska; Rina Febriana (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to determine the implementation of active and creative learning methods at TPA Al-Ikhlas, Kemuning District, Palembang City, and their impact on students' activeness. This research used a qualitative method with a field research approach. The subjects were 31 students consisting of 14 males and 17 females. Data were collected through observation, interviews, and documentation. The results showed that active and creative learning methods were implemented through Qur'an reading assistance, ice breaking, quizzes, worship practices, and creative activities. The implementation of these methods made students more active, focused, and confident during learning. Supporting factors include student enthusiasm, teacher support, and varied learning activities. Inhibiting factors include differences in student abilities and lack of focus during learning